Paying for gender? The gender price gap in Central Kenyan vegetable markets - Lutz Depenbusch (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
We analyze the gender price gap (GPG) in Central Kenyan vegetable markets. Exploiting differences in the combination of the gender of the household head, the person controlling production, and the seller, we control for other gender related influences. We cannot identify a significant GPG for the population as a whole but find an u-shaped relationship between the GPG and the sold quantities. Also, we observe that female control over marketing is negatively associated with the commercialization of vegetable trade. This indicates that besides the absence of an average GPG, women are disadvantaged in larger scale markets. These findings support recent experimental evidence that the GPG depends on the perceived competence and entitlement as women are traditionally active in small scale local vegetable trade but not in large scale trade in the survey region. Also, it is a warning that women might be left behind in an increasingly commercializing market, even though they traditionally controlled it.
Keywords: D63; J16; O13; Q12; Q13; 330; Gender; Gender Price Gap; Inequality; Agriculture; East Africa; Transaction costs